Investigation of Micropolar Hybrid Nanofluid (Iron Oxide–Molybdenum Disulfide) Flow Across a Sinusoidal Cylinder in Presence of Magnetic Field - Hosseinzadeh, Kh; Mardani, M. R.; Salehi, Sajad; Paikar, M.; Ganji, D. D. (International journal of applied and computational mathematics, 2021)
The purpose of this paper is to investigate the micropolar nanofluid flow across a sinusoidal cylinder in presence of the magnetic field. The base fluid is an equal mixture of ethylene glycol and water; also,ithybridized by iron oxide (Fe 3 O 4 ) andMolybdenum disulfide (MoS 2 ) nanoparticles.In this study, equations are transformed from PDEs to ODEs and solved by Rung-Kutta fifth-order. After solving the equations, it can be seen that various nondimension parameters are involved (e.g.micro-polar parameter, nanoparticle volume fraction, shape factor, and magnetic field parameter), therefore a sensitivity analysis is applied to investigate the effect ofinvolvedparameters. Besides, variation of Nusselt number and skin friction coefficient are studied.Further analysis showed that Nusselt number is an increasing function of volume fraction and increment in the magnetic field leads to higherskin friction coefficient.Also, whenmicro-gyrationis zero the microelements in the vicinity of the wall are unable to rotate, and by increasing micro-gyration parameters these microelements meet rotation.As a novelty, the hybrid Micropolar nanofluid suspends in mixture fluid flow in sinusoidal cylinder geometry have been investigated. The magnetic force and rotational velocity have been considered.